Principal Directions of the Development of Pedagogical Science in Poland: Historiographic Analysis - Viktoria Pavlovs’ka (Pedagogical Discourse, 2013)
The article deals with the analysis of the Polish pedagogical scientific thoughts and sources in the Republic of Poland, new works of the Polish pedagogues, and modern tendencies in education. It analyses scientific papers written by the Polish educators in such spheres of pedagogy as alternative pedagogy, andragogy, personalistic pedagogy, pedutolohiya, pedagogy of labour, pedagogy of culture, media pedagogy, special pedagogy, society pedagogy, ecology pedagogy, humanistic pedagogy, critical pedagogy, naturalistic pedagogy, pedagogy of care, postmodernist pedagogy. The analysis of pedagogical branches is made in the context of reforming the system of education in Poland and integration into the European Union. Historiographical approach is the study of historical and pedagogical knowledge. Historical and pedagogical studies considering education and training are the documentary and source base for pedagogical historiography. Studying the experience of Polish educators may be useful in reforming the education system in Ukraine.